Tipula (Vestiplex) pseudocoxitalis sp. nov., a new crane fly (Diptera, Tipulidae) from southwestern China - Starkevich, Pavel; Men, Qiu-Lei; Podėnas, Sigitas (Zootaxa, 2026)
A new crane fly species, Tipula (Vestiplex) pseudocoxitalis sp. nov., is described and illustrated based on material collected in Chongqing, China. An identification key is provided to distinguish males of the new species from other members of the T. (V.) coxitalis Alexander, 1935 species group.